Influence of deep rolling on surface layer condition and fatigue life of steel welded joints. (September 2022) - Dänekas, C.; Heikebrügge, S.; Schubnell, J.; Schaumann, P.; Breidenstein, B.; Bergmann, B.
Highlights: First application of deep rolling for the fatigue strength improvement of real scale welded joints made of structural steels. Investigation of the local weld toe geometry and stress concentration factor based on 3D-Scans. Investigation of the residual stress state after deep rolling of welded joints. Qualitative analysis of residual stresses, weld toe geometry and fatigue strength based on different deep rolling parameters. Abstract: Deep rolling is an established mechanical surface treatment method to modify surface and subsurface properties and increase the wear- and fatigue strength of metallic parts and components. However, until now, deep rolling has not been considered for use as a post treatment method of welded joints to extend fatigue life of steel constructions. In this study, butt joints made of construction steels S355J2+N and S355G10+M were treated by means of hydrostatic deep rolling with tool diameter. The surface and subsurface properties after treatment were quantified by roughness-, hardness and residual stress measurements. Reduced roughness of 50–80%, increase of surface near hardness of up to 45% and compressive residual stresses of up to - 1, 000 M P a were determined after deep rolling. Furthermore, the stress concentration factor of the weld toe was evaluated for each specimen based on surface scans. Due to the comparable low contact force of the deep rolling tool-process parameter combinations investigated, the stress concentration of the weld toe was mostly unaffected by deep rolling. However, a significant fatigue life improvement by deep rolling was determined for all test series, showing a maximum increase of FAT-class of approximately 60%. A tendency is shown that a higher tool diameter leads to higher fatigue life improvement.